Komparasi Jalur Moneter untuk Stabilitas Harga Dalam Kerangka Inflation Targeting Framework (Studi kasus pada interest rate, exchange rate dan credit channel) - Wahyudi, Setyo Tri; Zakaria, Rinny Apriliany; Badriyah, Nurul (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2019)
The monetary policy transmission mechanism has many ways in influencing inflation. This method became known as the monetary path. The use of appropriate channels in monetary policy will affect whether or not the objectives of the monetary policy are achieved. This study aims to determine which monetary path is appropriate for Indonesia, which is a developing country with an open economic system. The data used are secondary data taken from Bank Indonesia for the period 2005 to 2016. The research variables include inflation, BI-rate, credit interest rates (SBB), gross domestic product (GDP), exchange rate, bank reserve (BBR), and the amount of credit extended. This study focuses on the path of interest rates, exchange rates and bank credit using the Error Correction Model (ECM). The results of this study indicate that the right monetary path for Indonesia is the credit channel. This is because the value of the Error Correction Term (ECT) coefficient on the ECM model shows that the coefficient of the credit channel is smaller than the interest rate and exchange rate channel, which means that the imbalance that occurs can be resolved more quickly with the credit channel.